A Simple Technique for Sustaining Solar Energy Production in Active Convective Coastal Regions - Moses E. Emetere; Marvel L. Akinyemi; Etimbuk B. Edeghe (International Journal of Photoenergy)
The climatic factors in the coastal areas are cogent in planning a stable and functional solar farm. 3D simulations relating the surface temperature, sunshine hour, and solar irradiance were adopted to see the effect of minute changes of other meteorological parameters on solar irradiance. This enabled the day-to-day solar radiation monitoring with the primary objective to examine the best technique for maximum power generation via solar option in coastal locations. The month of January had the highest turbulent features, showing the influence of weather and the poorest solar radiance due to low sunshine hour. Twenty-year weather parameters in the research area were simulated to express the systematic influence of weather of PV performance. A theoretical solar farm was illustrated to generate stable power supply with emphasis on the longevity of the PV module proposed by introducing an electronic concentrator pillar (CP). The pictorial and operational model of the solar farm was adequately explained.